Supply chain control tower and the adoption of intelligent dock booking for improving efficiency - Wyciślak, Sławomir; Pourhejazy, Pourya (Frontiers in Energy Research, 2023)
Poor coordination at distribution centers is a prime source of supply chain delays and energy waste that can be avoided through real-time planning and enhanced visibility. As a modern logistics topic with implications for supply chain transformation, Intelligent Dock Booking (IDB) coordinates the incoming and outgoing shipments at distribution centers. The research on IDB is at the early development stage. This study contributes to the Supply Chain Control Tower (SCCT) by developing a conceptual model of IDB, identifying its implementation requirements, and exploring its impacts on the supply chain performance. The causal loops and stock/flow diagrams are used to investigate how several efficiency indicators like the number of cancellations, planning time, utilization of space for loading and unloading, and the duration of processing trucks at distribution centers can be improved. Further, real-time data integration, operational preconditions, automated scheduling, dynamic responsiveness, and interdepartmental integration are identified as the key implementation requirements. The findings provide a foundation for implementing IDB systems in SCCTs.